Major 20th century changes of the content and chemical speciation of organic carbon archived in Alpine ice cores: Implications for the long‐term change of organic aerosol over Europe. Issue 9 (14th May 2013) - Legrand, M.; Preunkert, S.; May, B.; Guilhermet, J.; Hoffman, H.; Wagenbach, D.
Abstract : [1] Dissolved organic carbon (DOC) and an extended array of organic compounds were investigated in an Alpine ice core covering the 1920–1988 time period. Based on this, a reconstruction was made of the long‐term trends of water‐soluble organic carbon (WSOC) aerosol in the European atmosphere. It is shown that light mono‐ and dicarboxylates, humic‐like substances, and formaldehyde account together for more than half of the DOC content of ice. This extended chemical speciation of DOC is used to estimate the DOC fraction present in ice that is related to WSOC aerosol and its change over the past. It is suggested that after World War II, the WSOC levels have been enhanced by a factor of 2 and 3 in winter and summer, respectively. In summer, the fossil fuel contribution to the enhancement is estimated to be rather small, suggesting that it arises mainly from an increase in biogenic sources of WSOC. Key Points: Increase of biogenic organic Aerosol over Europe during the 20th century Companion to DOI:10.1002/jgrd.50200 Companion to DOI:10.1002/jgrd.50201